Comparative Analysis of Different Forest Fire Susceptibility Models in Benguet, the Philippines - Poclis, Cindy E.; Tiburan, Cristino L., Jr.; Racelis, Diomedes A.; Visco, Roberto G.; Galang, Marco A.; Villareal, Jayric F. (2024)
Fire is a common threat to forests in our country. It is usually uncontrolled and consumes the natural fuels of the forest, affecting both the vegetation and the soil. In the Philippines, forest fires are mostly frequent in regions with naturally occurring vegetation that is highly susceptible to forest fire, and one of them is the Cordillera Administrative Region. This study was conducted to [1] determine forest fire occurrences in Benguet province, [2] generate forest fire hazard maps using three indices [structural fire index (SFI), fire risk index (FRI), and hybrid fire index (HFI)], and [3] recommend potential forest management strategies to reduce fire susceptibility or manage fire occurrence in the province. NDMI, elevation, slope, aspect, distance from roads, and vicinity to settlements were the influencing factors used in the occurrence of forest fires. Moreover, forest fire occurrences in the province were collected from DENR records. Results revealed that from 2019–2021, a total of 90 forest fire incidents were observed in the area. In terms of the indices, results showed that maps using HFI and FRI revealed better results than the SFI model. Furthermore, there were forest fire incidences that coincided with the FRI model, particularly in those areas identified as having high and very high susceptibility ratings.
Keywords: Forest fires; Hazards